Az első jugoszláv állam felbomlásához vezető strukturális problémák - Gulyás, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Yugoslavia was born twice (1918, 1945) and split twice (1941, 1991) during the short - 91 years - of its history, thus we think it is worth to analyze the reasons of those splits. We are concerned that the reasons - first of all the regional differences - causing the split the first Yugoslav state (1918-1941). In our paper we analyze how first Yugoslav state tried to overcome regional differences, and how it led to the split of the state.